The Sacred World Encounters with the World's Religions [ - Fisher (Upper Saddle River, NJ: Pearson Prentice-Hall, 2008)
System requirements for accompanying CD-ROM: MacIntosh ; Windows
To accompany textbook titled "Living religion / Mary Pat Fisher"
AUP
Keywords: Religion